A dynamic approach to the syntax-phonology interface: A case study of Greek - Anthi Revithiadou; Vassilios Spyropoulos (Interphases: Phase-theoretic Investigations of Linguistic Interfaces, 2009)
Current approaches to syntactic derivation capitalize on the notion of syntactic cycles either in the sense of phases (Chomsky 2000) or derivational cascades (Uriagereka 1999). Such models raise some interesting issues regarding the way in which phonology processes the syntactic output. In this paper we propose that the derivational status of syntactic material is reflected on the way PF organizes the output of syntax into phonological phrases. More specifically, based on evidence from the prosodification of clitic-doubled DP-objects in Greek, we argue that elements which exhibit derivational islandhood form independent phonological phrases and, significantly, are impervious to PF restructuring mechanisms. We further explore the limits of this isomorphism by investigating the derivational and prosodic status of preverbal Greek subjects and conclude that their syntactic non-islandhood is matched by an analogous behavior at the PF since they are subject to restructuring. This particular type of isomorphism provides empirical justification for drawing a distinction between two different implementations of Spell-Out, as originally proposed in Uriagereka (1999).